Neoadjuvant Immunotherapy and Intestinal Microbiota: Unraveling their roles in Anastomotic Leakage and Fistula after Colorectal Cancer Surgery: Neoadjuvant Immunotherapy and Intestinal Microbiota: Unraveling their roles in Anastomotic Leakage and Fistula after Colorectal Cancer Surgery - Araujo-Filho, Irami; Menseses Rêgo, Amália Cinthia (JOURNAL OF SURGICAL AND CLINICAL RESEARCH, 2024)
This comprehensive review explores the multifaceted relationship between neoadjuvant immunotherapy, intestinal microbiota alterations, and anastomotic leakage risk in patients undergoing colectomy for colon neoplasia. With the advent of immunotherapy, remarkably immune checkpoint inhibitors, there has been a significant shift in the treatment paradigms for various cancers, including colon neoplasia. These treatments, while effective, have been associated with changes in the intestinal microbiome, which, in turn, may influence wound healing and the integrity of anastomotic sites. The review delves into the complex interactions between the immune system and the gut microbiota, examining how immunotherapy-induced dysbiosis could disrupt the delicate balance necessary for optimal anastomotic healing. It discusses the role of specific bacterial species in modulating the immune response to cancer and their impact on the efficacy of immunotherapeutic agents. Moreover, the review highlights the potential mechanisms through which the microbiota-immune system interaction could affect surgical outcomes, focusing on the development of anastomotic leaks. The implications of these findings for clinical practice are discussed, including the need for targeted strategies to modulate the gut microbiota in patients undergoing immunotherapy and colectomy. Through this discussion, the review aims to provide insights into improving patient outcomes by integrating microbiome management into colon neoplasia patients' treatment and perioperative care.